(untitled) (Journal of Nepal Geological Society, 2010)
Micro textures of metabasics from the Tso-Morari region, Ladakh were studied in order to understand the evolutionary metamorphic history of eclogites. The mineral chemistry, paragenesis of mineral inclusions in garnet, and zoning in omphacite, garnet and amphibole suggest three main metamorphic stages: (i) an eclogite stage with late blueschist facies metamorphism, (ii) a medium-pressure amphibolite facies stage, and (iii) a low-pressure amphibolite to greenschist facies stage. The high Si content in phengite, presence of rutile besides almandine-rich garnet and omphacite in eclogites indicate the attainment of high pressures. Also, the textural features and composition of amphiboles indicate that blueschist facies conditions represented by growth of glaucophane at high pressure and low temperature were followed by a lower-pressure stage of metamorphism represented by partial and in some cases complete reaction of glaucophane to calcic green amphibole such as magnesio-hornblende. The relationships define a clock-wise P-T path with the involvement of an isothermal uplift path for the eclogites and associated garnet-amphibolites of Tso-Morari region.